Pyotr Kropotkin: foundations of anarchist prison abolition - Weide, Robert D. (Envisioning abolition, 2025)
This chapter examines the fascinating life and thought of Pyotr Kropotkin, arguably the most important figure in the anarchist tradition of prison abolition. Starting with his childhood, born into Russian nobility, the chapter traces his transition into an anarchist revolutionary that resulted, in part, from his experiences with incarceration, first as an officer in the Russian Army and later as a prisoner of Tsar Alexander III. The chapter recounts Kropotkin’s own experiences as a prisoner, both in Russia and later in France, and follows his travels from Russia and throughout Europe to his eventual return to Russian and passing in the wake of the Russian Revolution. Using his book In Russian and French Prisons as a primary text, along with related works composed over the course of his lifetime, the chapter traces Kropotkin’s thoughts on incarceration that laid the foundation for the important role of prison abolition in the anarchist revolutionary framework. It concludes with a discussion on why Kropotkin’s work and legacy have unfortunately been omitted from much of the contemporary prison abolition literature, particularly in the American context.